PENERAPAN TEORI SELF DISCLOSURE PADA GENERASI MILENIAL (PEMILIK SECOND ACCOUNT INSTAGRAM) - Zumiarti; Rahmad Surya (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
The millennial generation, which was born at the same time as technology, is close to technology, including the internet and today's social media, namely Instagram. The purpose of this study is to find self-disclosure or self-disclosure with freedom of expression and eliminate the feeling of insecurity that is felt by millennials on second Instagram accounts. One of the social media, namely Instagram, with its Stories feature, is currently not only a place to find friends or share information. But also to express feelings and express themselves by users. continues to increase until Instagram Stories becomes a place for self-disclosure. The method used by researchers is a qualitative descriptive method in which researchers conduct observations, interviews, and documentation of several informants who are randomly selected starting from the ages of 20 to 24 years (early adulthood). Based on this, this study discusses self-disclosure of the millennial generation in second Instagram accounts. The purpose of this study is to find out the forms and impacts of self- disclosure on second Instagram accounts. The theory used in this study is the Johari Windows theory with a qualitative approach and descriptive method. The results of the discussion explain that the biggest aspect of self-disclosure in the millennial generation is open self or open area, then there is also hidden self or hidden area, blind self or blind area and unknown self or unknown area. There are goals for self-expression, motivating others, social legitimacy and information sharing. Then there are positive and negative impacts after doing it on a second Instagram account.